HDX reveals the conformational dynamics of DNA sequence specific VDR co-activator interactions. Issue 1 (December 2017) - Zheng, Jie; Chang, Mi; Stites, Ryan; Wang, Yong; Bruning, John; Pascal, Bruce; Novick, Scott; Garcia-Ordonez, Ruben; Stayrook, Keith; Chalmers, Michael; Dodge, Jeffrey; Griffin, Patrick
Abstract The vitamin D receptor/retinoid X receptor-α heterodimer (VDRRXRα) regulates bone mineralization via transcriptional control of osteocalcin (BGLAP ) gene and is the receptor for 1α, 25-dihydroxyvitamin D3 (1, 25D3). However, supra-physiological levels of 1, 25D3 activates the calcium-regulating geneTRPV6 leading to hypercalcemia. An approach to attenuate this adverse effect is to develop selective VDR modulators (VDRMs) that differentially activateBGLAP but notTRPV6 . Here we present structural insight for the action of a VDRM compared with agonists by employing hydrogen/deuterium exchange. Agonist binding directs crosstalk between co-receptors upon DNA binding, stabilizing the activation function 2 (AF2) surfaces of both receptors driving steroid receptor co-activator-1 (SRC1) interaction. In contrast, AF2 of VDR within VDRM:BGLAP bound heterodimer is more vulnerable for large stabilization upon SRC1 interaction compared with VDRM:TRPV6 bound heterodimer. These results reveal that the combination of ligand structure and DNA sequence tailor the transcriptional activity of VDR toward specific target genes. The vitamin D receptor/retinoid X receptor-α heterodimer (VDRRXRα) regulates bone mineralization. Here the authors employ hydrogen/deuterium exchange (HDX) mass spectrometry to study the conformational dynamics of VDRRXRα and give mechanistic insights into how VDRRXRα controls the transcriptional activity of specific genes.